Important Relations of Classical Orthogonal Polynomials - Akacan, Ertan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
In this thesis, the theory of classical orthogonal polynomials which are Hermite, Laguerre and Jacobi polynomials will be studied. To begin with, we will supply an outline regarding the special functions. Followed by examples of properties for orthogonal polynomials in Chapter 2. In the third chapter, we begin classical orthogonal polynomials. To start with, we collate the orthogonal relation, Rodrigues formulas followed by the norm of the classical orthogonal polynomials. In the same chapter, the division of the collected examples of classical orthogonal polynomials into three chapters and assign them the weight function, intermission of the orthogonality, followed by differential equations, hypergeometric representation. To finalise we explain limit relations between polynomials. Keywords: Classical orthogonal polynomials, hypergeometric functions, second order differential equations, Rodrigues formula.

ÖZ: Bu tezde Hermite, Laguerre ve Jacobi olan klasik ortogonal polinomlar açıklanmıştır. Öncelikli olarak özel fonksiyonlar hakkında bilgi verilmiştir. İlerleyen bölümlerinde ise ortogonal polinomların özelikleri anlatılmıştır. Daha sonraki bölümde de klasik ortogonal polinomlar tanımlanarak ortogonallik ilişkisi anlatılmıştır. Rodrigues formülü ile klasik ortogonal polinomlar için norm hesabı yapılmıştır. Daha sonra ise klasik ortogonal polinom örneklerinin üç bölüme ayrıldığını görürüz. Bunların her biri için ayrı ayrı ağırlık fonksiyonları, ortogonallik aralığı, ikinci dereceden diferensiyel denklemi ve hipergeometrik gösterimi verilerek anlatılmıştır. Tezin son bölümünde de polinomlar arasındaki limit ilişkileri açıklanmıştır. Anahtar Kelimeler: Klasik ortogonal polinomlar, hipergeometrik fonksiyon, ikinci dereceden diferansiyel denklem, Rodrigues formülü.
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2020. Supervisor: Prof. Dr. Sonuç Zorlu Oğurlu.
Keywords: Mathematics; Orthogonal polynomials--Mathematics--Calculus; Classical orthogonal polynomials; hypergeometric functions; second order differential equations; Rodrigues formula